Applying the Decomposed Theory of Planned Behavior to Explore the Influencing Factors of NTC App Usage Intention. (31st December 2021) - Lin, Chih-Wei; Tsai, Yi-Xuan; Chang, Yu-Shan; Ding, Yun-Jhih; Liu, Jou-Chun; Lin, Yu-Sheng
Abstract : This research is aimed at exploring the influencing factors of users' behavioral intention toward the Nike Training Club (NTC) app, using the decomposed theory of planned behavior as the main research framework. In this study, users of the NTC app were the research objects. A total of 300 questionnaires were distributed on the Internet by the purposive sampling method. After excluding invalid questionnaires, a total of 280 copies were obtained. The effective questionnaire recovery rate was 93.33%. All data were verified by descriptive statistics and multiple regression analysis. The results of this study were as follows. First, the NTC app users were mostly female, aged between 19 and 25 years, were students, had a monthly income below 20, 000, and exercised one to two times a week. Second, the application of the decomposed theory of planned behavior found the following: perceived usefulness and perceived ease of use had positive effects on attitude; interpersonal influence and electronic word of mouth had a positive influence on subjective norms; self-efficacy and technology facilitation had positive effects on perceptual behavior control; and attitude, subjective norms, and perceptual behavior control all had a positive impact on behavioral intention. The NTC app users thought that the program interface was easy to use and that the app could help them effectively achieve the effect of exercise and fitness, which increased the benefits of continuously using the program.